PENERAPAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, DAN SHARE (SSCS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP - Irma Aryani; Rahmi Rahmi; Murni Murni; Riki Musriandi; Fitriyasni Fitriyasni; Maulida Maulida (Jurnal Dedikasi Pendidikan, 2024)
A quality learning process is influenced by the learning model used. A learning process that only listens to the teacher's explanation, does assignments, and focuses on books causes learning activities to become passive and there is a lack of student interaction. This has an impact on student learning outcomes. One model that involves students in learning is the Search, Solve, Create, and Share (SSCS) model. This research aims to determine the improvement in junior high school students' learning outcomes after implementing the SSCS learning model. This type of research is quantitative using Experimental Quasi. The subjects of this research were one experimental class, namely VIII-3, and one control class, VIII-4, SMP Negeri 3 Aceh Besar, each with 33 students. Data collection techniques use tests. The research results showed that the increase in learning outcomes for experimental class students was higher than that of the control class. The experimental class achieved 100% of the indicators of learning success/completion, namely ≥75% of students achieved a KKM ≥75 and there was an increase in student learning outcomes. The N-Gain test results show an increase in the moderate criteria, namely the experimental class is 0.69 and the control class is 0.49. Based on the results of the analysis, it can be concluded that the learning outcomes of students taught using the SSCS learning model are higher than the learning outcomes of students taught using the conventional learning model.